Psychometric Characteristics of a Commuting-to-School Behaviour Questionnaire for Families - Aranda-Balboa, María Jesús (Int J Environ Res Public Health, 2020)
The purposes of this study were: (a) to describe the patterns of modes of commuting to school (children) and to work (parents) separated by gender and age, (b) to validate the questions on children’s mode of commuting to and from school according to their parents, and (c) to analyse the reliability of a family questionnaire focused on commuting to school behaviours. A total of 611 parents (mean age: 43.28 ± 6.25 years old) from Granada (Spain) completed “Family commuting-to-school behaviour” questionnaire in two sessions separated by 14 days, (2016 and 2018). The validation between family and children’s questions was assessed using the Kappa and Spearman correlation coefficients, and the test–retest reliability within the family questions was assessed using the Kappa and the weighted Kappa. The children’s modes of commuting to school (mean age: 11.44 ± 2.77 years old) were mainly passive (57.7% to school) while parents’ modes of commuting to work were mainly active (71.6%). The validity of the mode of commuting was significant with high Kappa and Spearman coefficients. The test–retest reliability presented a good agreement for the mode of commuting to school in children, distance and time to school, and the mode of commuting to work in parents, while the questions on acceptable distance to walk or cycle to school showed a moderate to good agreement. The “Family commuting-to-school behaviour” questionnaire could be a useful tool to assess the mode of commuting of children, distance and time to school for researchers and practitioners.